f(x) = (x - 4 )(x - 6) = 0
because you can see when each factor is equal to zero
x - 4 = 0 ⇒ x = 4
x - 6 = 0 ⇒ x = 6
Answer:
5.96666666667
Step-by-step explanation:
I used a calculator
The speed to the island is x. The speed to return is x+5.
The distance is the same so, 2.5 multiplied by x = 2×(x+5).
It took 2.5 hrs to get there and 2 hrs to return. Now all we have to do is solve.
2.5*x = 2x + 10
.5x = 10
x=20
Therefore, the distance between islands is 2.5 × 20 = 50 miles.
hope this helps!
The expression that is equivalent to the given expression where the expression is given as (18)2⋅(19)2 is (18 * 19)^2
<h3>How to determine which expression is equivalent to the given
expression? </h3>
The expression is given as
(18)2⋅(19)2
Rewrite the above expression properly
So, we have
(18)^2 * (19)^2
The factors in the above expression have the same exponent.
So, the expression can be rewritten as
(18 * 19)^2
Hence, the expression that is equivalent to the given expression where the expression is given as (18)2⋅(19)2 is (18 * 19)^2
Read more about equivalent expression at
brainly.com/question/2972832
#SPJ1
1. Rational/The sum of two rationals is always rational
2. Irrational/ the sum of a rational and an irrational is always irrational
3. Irrational/The product of a nonzero rational and an irrational is always irrational
4. Rational/The product of two rationals is always rational
Pretty much all the irrational numbers are the ones with radical signs over them and the rational numbers are the fractions and whole numbers. Once you identify the two numbers to be rational or irrational, you can then find your answer within the second part of the answers.